Defining and surveying key populations at risk of HIV infection: Towards a unified approach to eligibility criteria for respondent-driven sampling HIV biobehavioral surveys. (August 2018) - Hakim, Avi J; Johnston, Lisa G; Dittrich, Samantha; Prybylski, Dimitri; Burnett, Janet; Kim, Evelyn
Substantial resources are invested in human immunodeficiency virus biobehavioral surveys using respondent-driven sampling for measuring progress towards the UNAIDS 90–90–90 goals and to obtain other essential data on key populations. Survey data are used to meet country needs as well those of development partners, whose data needs may sometimes diverge. Surveys using differing eligibility criteria impede comparisons across surveys. With scant literature and guidelines on how to approach eligibility criteria, diverse criteria are used within and across countries. We conducted a review of peer-reviewed human immunodeficiency virus respondent-driven sampling biobehavioral survey literature published through December 2013. We describe eligibility criteria of 137 articles representing 214 surveys. Reporting on age, risk behavior, and reference period of risk behavior was nearly universal; however, reporting on gender, geography, and language was less common. Multiple definitions were used for each criterion, making comparisons challenging. We provide a framework for how to approach defining eligibility to improve consistency and comparability across surveys.